Híbridos luminescentes da Rufinamida®: síntese e propriedades fotofísicas de 1,1-diflúor-1,3,5,2- oxadiazaborininos - Luz, Fábio Mulazzani da (2024)
This work presents the synthesis of luminescent Rufinamide® hybrids, describing all the synthetic methodologies used to obtain the target molecules. As first step, it describes the synthesis of substituted 1H-1,2,3-trichloroacetyl triazoles from the 1,3- dipolar cycloaddition reaction between substituted enones and benzylazides, obtaining them in yields ranging from 40 % to 75 %, two of which were synthetized for the first time (3ca and 3ea). After being synthesized, they were reacted against 2-aminopyridine and also 2-aminobenzo[d]thiazole in order to form amides. The amides formed were strategically designed to be bioisosteric to Rufinamide®. The methodology of this synthesis was successful, forming amides in high yields, between 56 and 90 %, and in this case, all the compounds in series 6 and 7 were never published (a total of 10 examples). These same amides went through photophysical tests but had no fluorescence results. Finally, the synthesized amides were reacted with BF3·OEt2 to form the oxadiazaborinic cycle, which has relevant and well-known photophysical properties. The reactions with BF3·OEt2 were successful, with their yield ranging from 62 to 87 %, and the compounds in series 9 and 10 were all first-time published compounds (10 examples). Absorption, emission, and fluorescence experiments were carried out on the difluororganoborous compounds synthesized and showed fluorescence, obtaining absorption and emission values in the 261 - 265 nm and 382 - 457 nm ranges, respectively. The compounds also obtained small Stokes shift values between 53 and 56 nm, exception of compound 10da which obtained a value of 128 nm, but their quantum yields (Φf) had low values in dichloromethane solution compared to 9,10-diphenylanthracene (DPA). The work also shows a theoretical discussion, based on the TD-DFT values, of the fluorescence results, and the analysis and study of the identification and characterization of the compounds by 1H, 13CH, 11B, 19F NMR, gas chromatography-mass spectrometry (GS-MS), high-resolution mass spectrometry (HRMS) and X-ray diffraction.